Influence of surgical bleeding on the relationship between admission coagulopathy and risk of massive transfusion: lesson from 704 severe trauma patients. Issue 2 (30th May 2016) - Charbit, J.; Lakhal, K.; Deras, P.; Dehon, A.; Latry, P.; Boissier, E.; Schved, J.‐F.; Capdevila, X.
Abstract : Background: This study hypothesized that the relationship between early coagulopathy and massive transfusion (MT) in trauma was highly dependent on the presence of surgical bleeding. Methods: Consecutive severe trauma patients admitted to our institution over a 4‐year period were included in this retrospective study. Surgical bleeding was defined as an injury requiring an invasive endovascular or surgical haemostatic procedure. The ability of prothrombin time ratio (PTr) and activated partial thromboplastin time ratio (aPTTr) to predict MT (≥10 units of packed red blood cells during the first 24 h) was determined by ROC curves. The strength of association and interaction between PTr, surgical bleeding and MT was assessed using a logistic regression analysis. Results: Among the 704 patients included (ISS 21·0 ± 16·2), MT rate was higher in patients with surgical bleeding than in those with no surgical bleeding (47% vs. 5%; P < 0·001). The global performance of PTr and aPTTr to predict MT was only fair in our study population (AUCs 0·83 and 0·81). MT rate was widely higher in the surgical bleeding group whatever the severity of coagulopathy ( P < 0·001). PTr was found to be significantly associated with TM [PTr ≥ 1·5, OR 23·6 (95% CI 13·4–41·7); PTr 1·2–1·5, OR 3·0 (95% CI 1·7–5·3)]. Corresponding ORs were reduced after adjusting for the surgical bleeding: 12·1 (95% CI 6·5–22·5) and 2·1 (95% CI 1·2–4·0), respectively. However, no significant interaction was found regression models. Conclusion: The strength of association between MT and coagulation status on admission was found strongly influenced by surgical bleeding. The admission coagulopathy monitoring in trauma patients without considering the surgical bleeding does not allow a reliable determination of MT probability.